2009
DOI: 10.1136/aim.2009.000802
|View full text |Cite
|
Sign up to set email alerts
|

Nice Guideline on Osteoarthritis: Is it Fair to Acupuncture? Yes

Abstract: The NICE Osteoarthritis Guideline Development Group (GDG) has been challenged for not using the available acupuncture evidence in the most appropriate manner in three crucial areas. This response explains the methods used by the GDG with particular reference to the economic analysis, and illustrates that the methods used were those most appropriate for developing a NICE clinical guideline. The cost-effectiveness conclusions made by the GDG are supported by the currently available evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This is one reason why acupuncture has received some attention in the UK [7,4,10,5]. Despite providing a lengthy introduction, the authors fail to cite academic literature that does not support CAM.…”
Section: Reporting Issuesmentioning
confidence: 99%
“…This is one reason why acupuncture has received some attention in the UK [7,4,10,5]. Despite providing a lengthy introduction, the authors fail to cite academic literature that does not support CAM.…”
Section: Reporting Issuesmentioning
confidence: 99%
“…Also, another recent metaanalysis of acupuncture for OA of the knee shows that there is a clinically irrelevant short-term and long-term improvement in pain and function compared with a sham control. 4 This underlines the issue raised in the guideline concerning heterogeneity of acupuncture trial outcomes.…”
Section: The Long-term Effectiveness Of Acupuncturementioning
confidence: 99%
“…This paper discusses three of the NICE conclusions that could be open to different interpretations, and a response is published in the accompanying paper. 4 …”
mentioning
confidence: 99%
“…[1][2][3] The NICE OA guideline, issued in February 2008, recommended against the use of electroacupuncture and also concluded that existing evidence was not of suffi cient consistency or strength to recommend the use of acupuncture. 4 Conversely, the NICE guidance for LBP, issued in May 2009, recommended that clinicians should consider offering a course of acupuncture therapy comprising a maximum of 10 sessions over a period of up to 12 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The approach adopted in the guideline was considered to represent a suitable commonality for all analyses, rather than using a 'no treatment' or 'usual care with no placebo' comparator for the analysis of some interventions, and a placebo comparator for others. 3 In the LBP guideline, one relevant economic evaluation was identifi ed, which examined the cost-effectiveness of acupuncture delivered by therapists trained in traditional Chinese medicine. 7 The study found that acupuncture was associated with base case cost-effectiveness estimates (£4241 per quality adjusted life year (QALY) gained) that are acceptable to NICE; Inconsistencies in NICE guidance for acupuncture: reanalysis and discussion Original paper accordingly, acupuncture therapy was recommended by the guideline.…”
Section: Introductionmentioning
confidence: 99%